1989
DOI: 10.1007/bf00195787
|View full text |Cite
|
Sign up to set email alerts
|

Effect of measuring volume length on two-component laser velocimeter measurements in a turbulent boundary layer

Abstract: The effects of finite measuring volume length on laser velocimetry measurements of turbulent boundary layers were studied. Four different effective measuring volume lengths, ranging in spanwise extent from 7 to 44 viscous units, were used in a low Reynolds number (Re o = 1440) turbulent boundary layer with high data density. Reynolds shear stress profiles in the near-wall region show that Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
3

Year Published

1991
1991
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 20 publications
2
7
3
Order By: Relevance
“…Johansson and Alfredsson [10] studied the effects of (spanwise) length of hot-wire on the fluctuating components of the streamwise velocity. Unlike the results of Johnson and Barlow [8], their measurements revealed a 10% reduction in u þ max as l þ z increased from 14 to 32. Above, y + = 15, their u + profiles from the various probes collapsed onto one curve but profiles of S u and F u showed more sensitivity to l þ z than observed in the LDA results reported by Johnson and Barlow [8].…”
Section: Introductioncontrasting
confidence: 71%
See 3 more Smart Citations
“…Johansson and Alfredsson [10] studied the effects of (spanwise) length of hot-wire on the fluctuating components of the streamwise velocity. Unlike the results of Johnson and Barlow [8], their measurements revealed a 10% reduction in u þ max as l þ z increased from 14 to 32. Above, y + = 15, their u + profiles from the various probes collapsed onto one curve but profiles of S u and F u showed more sensitivity to l þ z than observed in the LDA results reported by Johnson and Barlow [8].…”
Section: Introductioncontrasting
confidence: 71%
“…Unlike the results of Johnson and Barlow [8], their measurements revealed a 10% reduction in u þ max as l þ z increased from 14 to 32. Above, y + = 15, their u + profiles from the various probes collapsed onto one curve but profiles of S u and F u showed more sensitivity to l þ z than observed in the LDA results reported by Johnson and Barlow [8]. Johansson and Alfredsson [10] also compiled data of u þ max obtained by various researchers with varying l þ z values and concluded that u þ max decreased from 2.9 to 2.1 as l þ z increased from about 3 to 100.…”
Section: Introductioncontrasting
confidence: 71%
See 2 more Smart Citations
“…The resulting uncertainties for the statistical data derived from the LDA measurements presented in this paper are defined for the 95% confidence interval, based on the bootstrap re-sampling procedure [55] due to the unknown probability distributions of the velocity signals. This methods have been employed by many studies [56,57]. The analysis shows that the uncertainty of the data varied with the location of the measurement point, with the highest uncertainty being more than 3% for points at the edge of jet and less than 0.04% in the centre 3.…”
Section: Lda Arrangementmentioning
confidence: 99%